2007
DOI: 10.1111/j.1365-2591.2007.01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of pressure and flow rates during irrigation of a root canal ex vivo with three endodontic needles

Abstract: Finer diameter needles require increased effort to deliver the irrigant and result in higher intra-barrel pressure. The syringe and needles used tolerated the pressure developed. Irrigant flow rate should be considered as a factor directly influencing flow beyond the needle. Wide variations of flow rate were observed among operators. Syringe irrigation appears difficult to standardize and control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
2
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(162 citation statements)
references
References 36 publications
4
147
2
9
Order By: Relevance
“…Studies on the effectiveness of the irrigation examined parameters including anatomy of the root canal geometry, size and curvature, volume, pressure and flow rate of irrigant, the type, design, size, diameter and insertion depth of the irrigation needle (8,13,(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effectiveness of the irrigation examined parameters including anatomy of the root canal geometry, size and curvature, volume, pressure and flow rate of irrigant, the type, design, size, diameter and insertion depth of the irrigation needle (8,13,(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Cleaning of oval canals using ultrasonic or sonic Studies that evaluated methods of continuous irrigation found that the pressure and current of the irrigant flowing within the root canal generated a physical effect. 33,34) The EndoVac, a device that combines irrigation and suction of irrigant has been shown to leave significantly lower amounts of cutting residue in the apical area of root canals compared with conventional cleaning using a syringe. [35][36][37] In contrast, a comparison of the RinsEndo, a device for automatic irrigation, with conventional cleaning using a syringe found no significant difference in cleaning capability.…”
Section: Discussionmentioning
confidence: 99%
“…Important considerations are, however, the gauge of the needle used, the concentration of the irrigation solution, and the total volume and methods used. 4 In several studies mentioned in this review, it is not possible to divine all of these details. Also, the in-vitro experimental conditions differ from in-vivo studies in some aspects, among them, the volumes used for disinfection, the accessibility of microbes and the absence of other materials in in-vitro experiments which potentially protect bacteria in vivo.…”
Section: Commentarymentioning
confidence: 99%